Internet naming and addressing system security technology and application analysis - Cui-cui WANG; Zhi-wei YAN; Guang-gang GENG (网络与信息安全学报)
In order to ensure the security of domain name system and inter-domain routing system,Internet Engineering Task Force(IETF)proposed two kinds of security technology,namely domain name system security extention(DNSSEC)and resource public key infrastructure(RPKI).For the domain name system,DNSSEC added the digital signature to the original architecture of DNS using the public key infrastructure and it provided the authentication and integrity verification of DNS information,which became the anchor of domain name system security.For the inter-domain routing system,RPKI utilized the public key certificate to authenticate the ownership and usage rights of the Internet number resources and builds an Internet resource management system to enhance inter-domain routing security.Recently,the globally development of DNSSEC and RPKI were continuously expanding.In order to research the application of the two kinds of technology,Alexa top 1 million websites were taken as the data set to study and analyze the application status of DNSSEC and RPKI.